Management of Teacher Professionality Development in Primary Schools - Salsabilla, Imelia Sahda; Asiyah, Nur; Sutiyono, Agus (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2024)
This research aims to explore and understand aspects of Teacher Professional Development Management in Elementary Schools, focusing on three main things. First, examine teachers' perceptions of the professional development program implemented, including their views regarding its effectiveness, relevance, and benefits. Second, analyze the program's implications for teacher performance and motivation and the extent to which this program can increase teacher competence, morale, and dedication in the learning process. Third, the leadership role of school principals in supporting teacher professional development should be evaluated by looking at how school principals' support, guidance, and policies can strengthen teacher professionalism. This research uses a case study approach with qualitative methods to explore this phenomenon in depth. The research results show that effective school management, leadership support, and the availability of relevant resources and training methods are vital to increasing teacher competence and motivation. However, this research has limitations because it was only conducted in one school with a limited sample. For future research, it is recommended to involve a larger and more diverse sample from various schools to obtain more comprehensive and applicable data